Utilization of Artificial Intelligence in Facing the Covid-19 Pandemic: Systematic Literature Review - Muhamad Rizky; Aang Subiyakto (Jurnal Sistem Cerdas, 2022)
Abstract— COVID-19 virus is a virus that attacks the respiratory system which has become a pandemic, because it has spread to various countries and the world. Of course, this impact has brought difficulties in various sectors of human life. Artificial Intelligence (AI) is a computer system designed to follow human actions and thought patterns, so that they can have intelligence like humans. The presence of Artificial intelligence as a technology is able to play a role in producing innovations that are useful in dealing with the COVID-19 pandemic for human life. The purpose of this study was to find out how to use artificial intelligence in the face of the COVID-19 pandemic. The method used in this research is a literature study method. The results of this study are that artificial intelligence can be used in dealing with COVID-19 to help overcome problems that exist in various fields of human life.